KADAR KOLESTEROL DAN STATUS GIZI PEGAWAI DINAS KABUPATEN KLUNGKUNG - Ida Ayu Adhitya Prajadianti; Ni Nengah Ariati; I Dewa Nyoman Sudjana (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Abstract. Adult nutritional status can be monitored simply by using body mass index of nutritional status related to the advantages and disadvantages of weight. Overweight also can affect blood cholesterol levels. (Bannerman, 2005). Food consumption patterns of the community 18% have experienced similar changes with an increase in the popularity of fast food, an estimated 80% of lives could be saved if public consumption consume a complete nutrient content increased. The results of the Ministry of Health survey in the province of Bali to 2013, the data showed 10.5% of adults have a IMT 27 and 4.1% had a IMT ≥ 30 (Kemenkes, 2013). Bali provincial prevalence of overweight in the population above 18 years of age in males at 19.2% and 22.4% in women (Kemenkes, 2012). Data outpatient visits in public hospitals in Klungkung area is obtained most women with a IMT 26 have cholesterol levels of 25.2% and the majority of men with IMT 27 have cholesterol levels by 27.5%. This study have a purpose to get the nutritional status and blood cholesterol levels emplooyees of Klungkung Regency Public Health Department. This type of study is an observational study with cross sectional design. Conducted on 72 samples of employees in Klungkung Regency Public Health Department. This study was conducted in Klungkung Regency Public Health Department in June 2015. Keywords: Nutritional Status (IMT), Total Cholesterol Levels, Employee